Rol del docente en atención infantil y áreas de estimulación temprana de los niños de 0-36 meses de edad en la modalidad “creciendo con nuestros hijos” (cnh.) del distrito Latacunga en el año 2015: propuesta de una capacitación y diseño de una guía de actividades lúdicas en correspondencia con la edad para las educadoras. - Defaz Chicaiza, Rosa Imelda (2016)
This research is based on the Training and design of a guide to recreational activities in line with the developmental age of the child / aged 0 to 36 months, aimed at educators to solve the weakness of the teacher's role in child care specifically in the implementation of socio-educational for strengthening the areas of early stimulation of children / as under three years of modality "Growing with Our children" activities. Within this context theoretical aspects were considered from concepts, functions, methods, techniques and resources. For the construction of the proposal was deemed necessary field research in which techniques was used as the survey and observation, it took into account the needs of children, mothers and educators of the CNH family mode. From this perspective it became is known that should design the guide recreational activities for educators and training in their use; In this situation the thesis offered a specialized teachers work; a guide from recreational activities designed for the benefit of children from zero to thirty-six months in order to meet the needs of family educators. Finely implementation of the workshop on the guide recreational activities strengthened the family educators, raised awareness about the role that each plays in the proper application of play activities in early stimulation and therefore in child care. This research, once solved the problem was directly reflected in the beneficiaries such as children / as, parents and educators mode "Growing with Our Children" (CNH.) Of Latacunga district.